Effects of Recent/Healed Post-Extraction Protocols on Incisor and Canine Alignment During Fixed Orthodontic Appliance Therapy - Adedayo Ayomide Olabintan; Olayinka Donald Otuyemi; Kikelomo Adebanke Kolawole (Galenos Yayinevi, 2022)
Objective: The purpose of this study was to determine the effects of recent/healed post-premolar extraction protocol, gender, age, and dental arch on incisor and canine alignment during fixed orthodontic appliance therapy.Methods: The study sample consisted of 50 dental arches of patients undergoing fixed orthodontic appliance therapy. The arches were randomized into an equal number of recent and healed extraction groups. The orthodontic setup was instituted within 3-7 days and 5-6 weeks following first premolar teeth extractions in the recent and healed extraction groups, respectively.Orthodontic tooth alignment was carried out using 0.016-inch NiTi wires for 16 weeks. Study casts were made at baseline, 4, 8, 12-, and 16-week follow-up treatment. Little's Irregularity Index was used to assess orthodontic tooth alignment.Mann-Whitney U test was used to compare the alignment rates between groups, and multiple linear regression was used to predict the relationship of groups and sociodemographic factors to alignment rate. The statistical significance level was set at P < .05.Results: The mean daily incisor and canine alignment rates in the recent and healed extraction cases were 0.13 mm and 0.11 mm, respectively (P = .332), 0.12 mm in both males and females (P = .827), and 0.13 mm and 0.12 mm in the maxilla and mandible, respectively (P = .534). There was however a significant difference in the mean daily alignment rate between adolescents (0.15 mm) and adults (0.10 mm) (P = .019).Conclusion: The rate of incisor and canine alignment was not affected significantly by recent/healed post-extraction protocol, gender, and dental arch. However, the rate was significantly faster in adolescents.